2017
DOI: 10.1162/rest_a_00647
|View full text |Cite
|
Sign up to set email alerts
|

Much Ado about Nothing? New Evidence on the Effects of Payday Lending on Military Members

Abstract: We evaluate the effect that payday loan access has on credit and labor market outcomes of individuals in the U.S. Army. Using the conditional random assignment of service members to different locations, we employ three identification strategies: cross-sectional variation in state policies, within-term variation in payday lending access, and a differencein-difference analysis using the national Military Lending Act. We find few adverse effects of payday loan access on service members when using any of these met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…The motivation for this law as articulated by the U.S. Department of Defense, which lobbied for its passage, is that payday loans are predatory and create financial distress, which compromises military readiness and increases vulnerability to bribes and blackmail (U.S. Department of Defense, 2006). Despite the intentions behind the law, Carter and Skimmyhorn (Carter and Skimmyhorn, 2017) estimate that it has had no impact on a variety of labor market or credit outcomes for members of the U.S. Army.The Credit Card Accountability Responsibility and Disclosure (CARD) Act of 2009 is another variant of a usury law. In addition to limiting interest rate increases for credit cards, the CARD Act placed restrictions on non-interest credit card fees-including over-limit fees, late payment fees, and inactivity fees.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The motivation for this law as articulated by the U.S. Department of Defense, which lobbied for its passage, is that payday loans are predatory and create financial distress, which compromises military readiness and increases vulnerability to bribes and blackmail (U.S. Department of Defense, 2006). Despite the intentions behind the law, Carter and Skimmyhorn (Carter and Skimmyhorn, 2017) estimate that it has had no impact on a variety of labor market or credit outcomes for members of the U.S. Army.The Credit Card Accountability Responsibility and Disclosure (CARD) Act of 2009 is another variant of a usury law. In addition to limiting interest rate increases for credit cards, the CARD Act placed restrictions on non-interest credit card fees-including over-limit fees, late payment fees, and inactivity fees.…”
mentioning
confidence: 99%
“…There is some evidence that payday borrowing helps households smooth consumption (Zinman, 2010;Morse, 2011) and that it does not have adverse impacts on 15 http://files.consumerfinance.gov/f/documents/CFPB_Proposes_Rule_End_Payday_Debt_Traps.pdf 12 credit scores or job performance (Bhutta, 2014;Bhutta et al, 2015;Carter and Skimmyhorn, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Karlan and Zinman (2010) demonstrated that the expansion of credit in South Africa, even at 200% annual interest rates, still improved economic outcomes for borrowers. Carter and Skimmyhorn (2016) showed that exposure to payday loans does not negatively affect labor and credit outcomes for military personnel, while Zinman (2010) provided evidence that if access to payday loans is restricted by regulation, payday borrowers shift into inferior and more harmful substitutes. 16 It is possible to conclude that if bad financial decisions are made due to a lack of self-control and poor financial decisions lead to poverty, then a lack of self-control is a cause of poverty.…”
Section: Non-standard Preferencesmentioning
confidence: 99%
“…64 Department of Defense Directive 1315.07 and Army Regulation 600-14 provide the regulatory basis for CRA. Other researchers have used versions of this identification strategy, including Angrist and Johnson (2000), Carrell and Zinman (2014), and Carter and Skimmyhorn (2016). Army Regulation 600-13 provides the further stipulation that female soldiers cannot be assigned to units that have a routine mission to engage in direct combat, or to units which collocate with units assigned a direct combat mission.…”
Section: A Conditional Random Assignmentmentioning
confidence: 99%